2019
DOI: 10.5114/aoms.2018.77733
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 promotes chronic lymphocytic leukemia progression through upregulating SMYD3 expression

Abstract: IntroductionThis study was designed to investigate the roles of STAT3 and SMYD3 in chronic lymphocytic leukemia and the regulatory relationship between STAT3 and SMYD3 in chronic lymphocytic leukemia.Material and methodsThe expression of STAT3 and SMYD3 was determined by RT-qPCR and western blot in chronic lymphocytic leukemia samples and cells (MEC1, CLL). Small interfering RNA was used to knock down the mRNA level of STAT3 and the pcDNA3.1-SMYD3 plasmid was used to construct a SMYD3 overexpression model. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In our study, we also monitored levels of activated STAT proteins and found that the presence of MSC CM results in activation of STAT3 and STAT6 ( Figure 4 ). Increased activation of STAT3 has been associated with malignant cell transformation and drug-resistant tumors [ 44 , 46 , 47 ]. Moreover, exposure of CML cells to MSC CM caused an increase in pSTAT3 and consequently increased the expression of STAT3-regulated genes such as Bcl-xl, Mcl-1, and survivin [ 46 ].…”
mentioning
confidence: 99%
“…In our study, we also monitored levels of activated STAT proteins and found that the presence of MSC CM results in activation of STAT3 and STAT6 ( Figure 4 ). Increased activation of STAT3 has been associated with malignant cell transformation and drug-resistant tumors [ 44 , 46 , 47 ]. Moreover, exposure of CML cells to MSC CM caused an increase in pSTAT3 and consequently increased the expression of STAT3-regulated genes such as Bcl-xl, Mcl-1, and survivin [ 46 ].…”
mentioning
confidence: 99%
“…The STAT3-SMYD3 axis promotes carcinogenesis, since high SMYD3 levels show a negative correlation with suppression of cell proliferation and invasion capacity. Downregulation of the phosphorylation of STAT3 by means of the STAT3 inhibitor WP1066 suppressed STAT3 binding to the SMYD3 promoter, consequently inhibiting SMYD3 gene expression ( Ma et al., 2019 ; Lin et al., 2019 ). Ectopic overexpression of SMYD3 in a human leukaemia cell line induced mRNA expression of the c-Met oncogen, thereby providing a rationale to test SMYD3 inhibitors for the treatment of leukaemia ( Zou et al., 2009 ).…”
Section: Blood Cell Cancersmentioning
confidence: 99%
“…H4K20me1 promotes association of L3MBTL1 with the 5′ long terminal repeat SYMD2 inhibition reactivated HIV-1 ( Boehm et al., 2017 ) SMYD3 Human primary monocytes Decreased SMYD3 mRNA and cell proliferation 18 h after IFNγ treatment of CSF1 differentiated primary human macrophages ( Yildirim-Buharalioğlu et al., 2017 ) SMYD3 Patients with diabetes (T1DM and T2DM), N = 19-21 Under hyperglycaemic conditions, SMYD3 activates S100A12 expression by methylation of S100A12 promoter in M1 macrophages ( Mossel et al., 2020 ) SMYD3 Many cell lines SMYD3 in T cell lines and primary T cells directly interacts with HTLV-1 Tax and supports Tax cytoplasmic localisation ( Yamamoto et al., 2011 ) SMYD3 Female C57BL/6 mice, N = 3 SMYD3 catalyses H3K4me3 in the promoter region of the foxp3 gene and regulates its expression in iTreg cells Inhibition of SMYD3 impairs iTreg cell formation. SMYD3 KO mice infected with respiratory syncytial virus display exaggerated inflammatory responses and aggravation of the disease ( Nagata et al., 2015 ) SMYD3 Human Hodgkin lymphoma L1236 and L428 cell lines SMYD3 participates in Hodgkin lymphoma development via H3K4 methylation at the promoter of 15-LOX-1 ( Liu et al., 2012 ) SMYD3 Human chronic lymphocytic leukaemia MEC1 cell line Patients with leukaemia, N = 20 Many human chronic lymphocytic leukaemia cell lines SMYD3 upregulation by STAT3 in chronic lymphocytic leukaemia The STAT3-SMYD3 axis promotes carcinogenesis, since high SMYD3 levels showed a negative correlation with suppression of cell proliferation and invasion capacity Downregulation of the phosphorylation of STAT3 suppresses STAT3 binding to the SMYD3 promoter and SMYD3 expression ( Ma et al., 2019 ; Lin et al., 2019 ) SMYD3 Human leukaemia K562 and HL- 60 cell lines Overexpression of SMYD3 in a leukaemia cell line induces c-Met expression ( Zou et al., 2009 ) SMYD3 Patients with human papilloma virus-negative squamous cell carcinoma of the head and neck, N = 364, and derived cell lines Inhibition of SMYD3 causes CXCL9, CXCL10, CXCL11 and TAP1 upregulation in human papilloma virus -...…”
Section: Conclusion and Further Directionsmentioning
confidence: 99%
“…The STAT3-SMYD3 axis promotes carcinogenesis, since high SMYD3 levels show a negative correlation with suppression of cell proliferation and invasion capacity. Downregulation of the phosphorylation of STAT3 by means of the STAT3 inhibitor WP1066 suppressed STAT3 binding to the SMYD3 promoter, consequently inhibiting SMYD3 gene expression (Ma et al 2019;F. Lin et al 2019).…”
Section: Smyd3mentioning
confidence: 99%